Advanced artificial intelligence self balanced robot for home security - Shourove, MD. Niaz Sharif; Mahmud, Khaled; Rahman, Mafruda; Rahman, Tanzim (BRAC University, 2018)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2017.